2009
DOI: 10.1097/meg.0b013e328323aadd
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder wall variceal haemorrhage with associated rupture: a rare cause of mortality in the cirrhotic patient

Abstract: Gallbladder wall varices are unusual ectopic varices, which occur in the setting of portal hypertension, usually but not universally associated with portal vein thrombosis. Rupture of these varices may lead to life-threatening intra abdominal haemorrhage and is associated with a high mortality rate. We report a case of gallbladder wall variceal haemorrhage in a cirrhotic patient with patent transjugular intrahepatic portosystemic shunt, which resulted in death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Gallbladder's function and mobility are usually not affected by the presence of varicose veins (3). Very few cases have been reported of bleeding varices of the gallbladder as a cause of death (1). The bleeding may occur directly into the abdominal cavity or, as in the present patient, into the gallbladder.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Gallbladder's function and mobility are usually not affected by the presence of varicose veins (3). Very few cases have been reported of bleeding varices of the gallbladder as a cause of death (1). The bleeding may occur directly into the abdominal cavity or, as in the present patient, into the gallbladder.…”
Section: Discussionmentioning
confidence: 59%
“…These are ectopic varices that can develop in patients with portal hypertension, particularly in patients with occlusion of the portal vein. Its incidence is uncertain, but it has been estimated at 12-30% in the field of portal hypertension (1,2). They are usually located in the gallbladder and bile ducts where they can coexist and are usually asymptomatic (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reports of rupture of other intraabdominal vessels, including the mesenteric vein, umbilical vein, omental vein, gallbladder wall vein and retroperitoneal veins. [15][16][17][18][19] Hemoperitoneum has rarely been reported in schistosomiasis. Picaud et al 20 reported a case of hemoperitoneum from fallopian tube schistosomiasis from S intercalatum.…”
Section: Discussionmentioning
confidence: 99%